Transivitas Teks Mantra Warok Aji Gebyagan Pada Paguyuban Reyog Ponorogo - Alip Sugianto (Universitas Muhammadiyah Makassar, 2020)
Abstract. Alip Sugianto, 2020, The Aji Gebyagan spell is a warok mantra as an introduction to the Gebyagan ritual. Spell data were analyzed using the transiveness of the Linguistic Functional Systemic approach. The aim of this research is to find out more deeply the meaning of the spell of aji gebyagan and to reveal the ideational meaning. The results obtained by verbal processes 33%, attributive relational processes 33%, relational identification processes 25% and behavioral processes 9%. The data shows that the dominance of attributive verbal and relational factors indicates that warok has a closeness in mental processing that is reflected in the spell to get the blessing of God. In addition, there is also a behavioral process as the goal of the spell of safety in the Reyog Ponorogo performance.